Increasing Student Anxiety During Offline Learning Post Covid 19 - Livana PH; Dona Yanuar Agus Santoso; Sri Mulyani; Amin Kuncoro; Haeril Amir; Titik Suerni (Global Health Science Group, 2023)
Post-Covid-19 has changed student life, where the learning system that is usually carried out online has changed to offline. This method is almost applied all over the world after Covid 19, including Indonesia. The offline learning process causes students to experience anxiety. The purpose of this study is to determine the level of student anxiety in post-covid 19 offline learning. Quantitative research has been carried out using a descriptive approach. The sample of this research is nursing students with a total sample of 78 people. Data was collected using a questionnaire that was loaded in the Google form. Data were analyzed univariately using a frequency distribution. The results showed that the cause of anxiety was due to learning assignments.